RSUME inhibits VHL and regulates its tumor supressor function - Gerez, Juan Atilio (2015)
Somatic mutations or loss of von Hippel-Lindau (pVHL) happen in the majority of VHL disease tumors, which present a constitutively active Hypoxia Inducible Factor (HIF), essential for tumor growth. Recently described mechanisms for pVHL modulation shed light on the open question of the HIF/pVHL pathway regulation. The aim of the present study was to determine the molecular mechanism by which RSUME stabilizes HIFs, by studying RSUME effect on pVHL function and to determine the role of RSUME on pVHL-related tumor progression. We determined that RSUME sumoylates and physically interacts with pVHL and negatively regulates the assembly of the complex between pVHL, Elongins and Cullins (ECV), inhibiting HIF-1 and 2alpha ubiquitination and degradation. We found that RSUME is expressed in human VHL tumors (renal clear-cell carcinoma (RCC), pheochromocytoma and hemangioblastoma) and by overexpressing or silencing RSUME in a pVHL-HIF-oxygen-dependent degradation stability reporter assay, we determined that RSUME is necessary for the loss of function of type 2 pVHL mutants. The functional RSUME/pVHL interaction in VHL-related tumor progression was further confirmed using a xenograft assay in nude mice. RCC clones, in which RSUME was knocked down and express either pVHL wt or type 2 mutation, have an impaired tumor growth, as well as HIF-2alpha, vascular endothelial growth factor A and tumor vascularization diminution. This work shows a novel mechanism for VHL tumor progression and presents a new mechanism and factor for targeting tumor-related pathologies with pVHL/HIF altered function.